Transcriptional profiling of the postnatal brain of the Ts1Cje mouse model of Down syndrome - Tan, Kai Leng; Ling, King Hwa; Hewitt, Chelsee A.; Cheah , Pike See; Simpson, Ken M.; Gordon, Lavinia; Pritchard, Melanie A.; Smyth, Gordon K.; Thomas, Tim; Scott, Hamish S. (Elsevier, 2014)
The Ts1Cje mouse model of Down syndrome (DS) has partial trisomy of mouse chromosome 16 (MMU16), which is syntenic to human chromosome 21 (HSA21). It develops various neuropathological features demonstrated by DS patients such as reduced cerebellar volume [1] and altered hippocampus-dependent learning and memory [2] and [3]. To understand the global gene expression effect of the partially triplicated MMU16 segment on mouse brain development, we performed the spatiotemporal transcriptome analysis of Ts1Cje and disomic control cerebral cortex, cerebellum and hippocampus harvested at four developmental time-points: postnatal day (P)1, P15, P30 and P84. Here, we provide a detailed description of the experimental and analysis procedures of the microarray dataset, which has been deposited in the Gene Expression Omnibus (GSE49050) database.